Addiction, representation and the experimental novel, 1985-2015 - Diehl, Heath A. (Anthem Press, 2020)
The book analyzes the practices and politics of reading the experimental addiction novel, and outlines both a practice and an ethics of reading that advocates for a more compassionate response to addicts than the Western realistic novel traditionally has offered.